Lacosamide Induced Psychosis. Issue 5 (September 2015) - Pinkhasov, Aaron; Lam, Timothy; Hayes, Dillon; Friedman, Michelle; Singh, Deepan; Cohen, Henry
<x xml:space="preserve">Abstract</x> Abstract Lacosamide (LCM) is an antiepileptic medication used as an adjunctive treatment for partial seizures. Psychosis associated with LCM use is a rarely documented phenomenon, which may be difficult to detect in the context of the often complicated clinical presentation of epilepsy. We report the development of psychosis in a young woman after the use of LCM, which subsequently resolved with its discontinuation. The possible differential diagnosis and pharmacokinetic nuances are discussed. This is the first case report of LCM-induced psychosis in the United States.